2004
DOI: 10.1373/clinchem.2003.022061
|View full text |Cite
|
Sign up to set email alerts
|

Highly Recurrent RET Mutations and Novel Mutations in Genes of the Receptor Tyrosine Kinase and Endothelin Receptor B Pathways in Chinese Patients with Sporadic Hirschsprung Disease

Abstract: Background: Hirschsprung disease (HSCR) is a congenital disorder characterized by an absence of ganglion cells in the nerve plexuses of the lower digestive tract.HSCR has a complex pattern of inheritance and is sometimes associated with mutations in genes of the receptor tyrosine kinase (RET) and endothelin receptor B (EDNRB) signaling pathways, which are crucial for development of the enteric nervous system. Methods: Using PCR amplification and direct sequencing, we screened for mutations and polymorphisms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 44 publications
3
44
1
Order By: Relevance
“…Homozygotes of both the A allele of c135 G>A (A45A) and G allele of c2307T>G (L769L) was the most frequent genotype in HSCR patients (36%) while heterozygotes of both polymorphic sites were most common in controls (36%). The results were similar with the Hong-Kong studies (Garcia-Barcelo et al 2004) but different with the Caucasian populations (Borrego et al 1999;Fitze et al 1999). Furthermore, all but two of the LSA/TCA patients were homozygous for allele A of c135G>A and allele G of c2307T>G (82%).…”
Section: Ret Genotypessupporting
confidence: 84%
See 1 more Smart Citation
“…Homozygotes of both the A allele of c135 G>A (A45A) and G allele of c2307T>G (L769L) was the most frequent genotype in HSCR patients (36%) while heterozygotes of both polymorphic sites were most common in controls (36%). The results were similar with the Hong-Kong studies (Garcia-Barcelo et al 2004) but different with the Caucasian populations (Borrego et al 1999;Fitze et al 1999). Furthermore, all but two of the LSA/TCA patients were homozygous for allele A of c135G>A and allele G of c2307T>G (82%).…”
Section: Ret Genotypessupporting
confidence: 84%
“…The RET mutation rate in our HSCR patients seems to be low compared with those reported in other populations. In general, studies on sporadic HSCR yield lower frequencies of RET mutation studies than the familial cases (7-20% compared with 50%; Angrist et al 1995;Edery et al 1994;Garcia-Barcelo et al 2004;Garcia-Barcelo et al 2003;Romeo et al 1994;Sakai et al 2000;Seri et al 1997;Svensson et al 1998). However, germline RET mutation is associated with only 3% of a population-based series of isolated HSCR (Svensson et al 1998).…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, this is the first study that has used a fluorescence-based SNP detection assay for genotyping RET-protooncogene and NRG1, as previous studies have usually used PCR-direct sequencing, single-stranded conformation polymorphisms and restriction fragment length polymorphisms. 5,13,14,16,20,21 This fluorescence-based technique relies on different properties of two probes that are specific to the alleles of interest, each labeled with different fluorescent markers. It offers several advantages compared with older techniques; not only does it feature high specificity and accuracy, but also not requiring a post-amplification step reduces the time and cost of genotyping.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Recent studies have suggested the RET-protooncogene as a major locus involved in HSCR pathogenesis. [11][12][13] Single-nucleotide polymorphisms (SNPs) of the RET-protooncogene have been demonstrated to have an association with HSCR in various studies in Asians, [12][13][14][15][16] the majority of these studies were conducted in East Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…The mutation rate of RET among Asians is from 3.6 to 24% (Wu et al 2005;Sakai et al 2000;Tou et al 2006;Garcia-Barcelo et al 2004). Considering missense mutations in sporadic HSCR alone, figures reported are 7.1% for the Japanese (Sakai et al 2000), 24% for Hong Kong Chinese , and 0% for Taiwan Chinese (Wu et al 2005).…”
Section: Discussionmentioning
confidence: 97%